The effects of ethyl-2-cyanoacrylate and butyl-2-cyanoacrylate in the process of bone healing in rats. A controlled experimental study - Palacio, Evandro Pereira; Pereira, Gilberto José Cação; Silvares, Paulo Roberto De Almeida; Stasi, Gabriel Guimarães Di; Staut, Caio De Andrade; Sardenberg, Trajano (Sociedade Brasileira de Ortopedia e Traumatologia, 2018)
ABSTRACTObjective:Synthetic adhesives are used by various medical specialties, especially in surgery; however, studies reporting their use in orthopedic practice are scarce. The aim of this study was to compare the results in using ethyl-2-cyanoacrylate or butyl-2-cyanoacrylate in the treatment of fractures in rats.Methods:This was an experimental prospective controlled study in 90 rats, with humerus, femur, and tibia fractures, treated with ethyl-2-cyanoacrylate (SB group; n = 45) or butyl-2-cyanoacrylate (HA group; n = 45). Biomechanical and histomorphometric analyses were performed at three different moments (60, 120, and 180 days); besides a clinical study performed weekly by measurement of the animals body mass.Results:No differences were observed regarding body mass (p = 0.07). In both groups, there were no significant differences regarding maximum load (p = 0.6), yield point strength (p = 0.6), and stiffness coefficient (p = 0.4) of the femurs. The same was observed in tibias for maximum load (p = 0.4), yield point strength (p = 0.7), and stiffness coefficient (p = 0.6). The humerus from both groups had similar bone callus area (p = 0.66). In both groups, there were no statistical differences related to inflammatory cells (p = 0.4), osteoblasts (p = 0.2), and osteoclasts (p = 0.2).Conclusion:Ethyl-2-cyanoacrylate was more effective than butyl-2-cyanoacrylate in the treatment of fractures in rats.

RESUMOObjetivo:Os adesivos sintéticos são usados em várias especialidades médicas cirúrgicas, contudo, os estudos que relatam seu uso na prática ortopédica são escassos. O objetivo deste trabalho foi comparar os resultados do uso do etil-2-cianoacrilato e do butil-2-cianoacrilato no tratamento de fraturas em ratos.Métodos:Foi realizado um estudo experimental, prospectivo e controlado em 90 ratos com fraturas de úmero, fêmur e tíbia, tratados com etil-2-cianoacrilato (grupo SB; n = 45) ou butil-2-cianoacrilato (grupo HA; n = 45). Foram realizadas análises biomecânicas e histomorfométricas em três momentos (60, 120 e 180 dias), além do estudo clínico pela aferição semanal da massa corporal dos animais.Resultados:Não foram observadas diferenças relacionadas à massa corporal dos animais (p = 0,07). Os fêmures de ambos os grupos não apresentaram diferença com relação à carga máxima (p = 0,6), limite de elasticidade (p = 0,6) e coeficiente de rigidez (p = 0,4). Analisando-se as tíbias, o mesmo foi observado com relação à carga máxima (p = 0,4), ao limite de elasticidade (p = 0,7) e ao coeficiente de rigidez (p = 0,6). Os úmeros de ambos os grupos apresentaram a mesma área de calo ósseo formado (p = 0,66). Em ambos os grupos, não houve diferença estatística relacionada ao número de osteoblastos (p = 0,2), osteoclastos (p = 0,2) e células inflamatórias (p = 0,4).Conclusão:O etil-2-cianoacrilato foi mais eficaz do que o butil-2-cianoacrilato no tratamento de fraturas em ratos.
Efeitos do etil-2-cianoacrilato e do butil-2-cianoacrilato no processo de consolidação óssea em ratos. Estudo experimental controlado
Keywords: Cyanoacrylates; Tissue adhesives; Fractures, bones; Fracture healing; Cianoacrilatos; Adesivos teciduais; Fraturas ósseas; Consolidação da fratura